Need Analysis: Developing Cross Cultural Understanding Material on Voluntary Program at English Education Department of Pancasakti University in Tegal - Yuvita Yuvita; Eva Fatimah (Metaphor, 2020)
Voluntary Program is one of the excellencies program in English department of Pancasakti University Tegal that brings international volunteers to join the teaching learning process and achieve the goals of the program. This study aims at figuring out the needs of students in developing the materials of cross cultural understanding. It was conducted at the English Education Department, Faculty of Teacher Training Pancasakti University in the even semester of the academic year 2018/2019. The data were collected from a questionnaire, classroom observation, and focus group discussions. The results of this study present the students’ perceptions on the teaching and learning process of cross cultural understanding classes attended, the problems encountered and its alternative solutions, and the materials of cross cultural understanding needed in the classes in order to increase students’ intercultural competence. To conclude, this program is sufficiently beneficial for increasing students’ motivation in learning English and to have intercultural competence by learning the cross cultural understanding.